Concurrent H2 Generation and Formate Production Assisted by CO2 Absorption in One Electrolyzer. Issue 11 (7th October 2021) - Cheng, Hongfei; Liu, Yumei; Wu, Jiawen; Zhang, Zheng; Li, Xiaogang; Wang, Xin; Fan, Hong Jin
Abstract: Electrolyzers coupling electrocatalytic hydrogen evolution with oxidation reactions of small organic molecules have the merits of reducing cell voltage and generating high‐value products. Herein, an electrolyzer is designed and optimized that can simultaneously achieve efficient hydrogen generation at the cathode, CO2 absorption by the catholyte, and methanol upgrading to formate at the anode. For these purposes, transition metal phosphides are used as the low‐cost catalysts. The unique electrolyzer exhibits a low working voltage of 1.1 V at 10 mA cm −2 . Under optimal conditions, the Faraday efficiencies of hydrogen evolution and formic acid conversion reactions, which are the reaction products at the cathode and anode, respectively, are nearly 100% at various current densities from 10 to 400 mA cm −2 . Meanwhile, the CO2 absorption rate is about twice that of the hydrogen generation rate, which is close to the theoretical value. An innovative and energy‐efficient strategy is presented in this work to realize simultaneous hydrogen production and CO2 capture based on low‐cost catalyst materials. Abstract : A trifunctional electrolyzer has been designed to simultaneously achieve electrocatalytic hydrogen generation, CO2 capture, and methanol upgrading to formate. By using low‐cost transition metal phosphides as the catalysts, the cell voltage is ≈1.1 V at 10 mA cm −2 . The Faraday efficiencies of H2 and formate are nearly 100%.